Counseling Psychology: From Defining the Field to Promoting World Peace. (April 2019) - Whiteley, John M.
Dr. John Whiteley, the founding Editor and original publisher of The Counseling Psychologist, discusses foundational and historical resources for psychologists to commemorate the 50th anniversary of the Journal. In this paper, he introduces online resources he would like to share with readers, including documents that were defining for the field of counseling psychology. These resources are presented within the context of the seven defining historical periods of the profession, from 1908 to the present.